PENGARUH PERSEPSI KUALITAS PRODUK, CITRA MEREK DAN PROMOSI TERHADAP MINAT BELI KONSUMEN BAN ACHILLES DI JAKARTA SELATAN - Endro Arifin; Achmad Fachrodji (Universitas Mercu Buana, 2015)
Abstarct. This study aims to examine and analyze the influence of Perceived Quality, Brand Image, and Promotionon Purchase Intention of the Achilles consumer in South Jakarta. Preliminary research data was secondary data from the Achilles. Research data was from questionnaires that‘s distributed tothe respondents. The sampling method use disincidental sampling by reason of ease to get respondens. By using the formulaTabachnickand Fidell, the number of samplesis determined amounted to 100 respondents, whocame fromeight storesAchillesin South Jakarta.The analytical method usedissimple and multiple linear regression. The results showed that the brand image partially significant effect on purchase intention. While the perceived quality and promotion partially have no significant effect on purchase intention. Simultaneously, the third free variable, that are perceived quality, brand image and promotion significantly effect on purchase intention.Keywords: Perceived Quality, Brand Image, Promotion, and Purchase Intention and Achilles Tyre